(untitled) (Heritage, 2023)
Peć kaza found a place in the works of numerous travel writers such as Ami Boué, Dr. Josef Miller, Ivan Franjo Jukić, Gedeon Josif Jurišić, Aleksandar Giljferding and others who spoke of it as an unsafe territory "where everyone was a public hajduk". It was for this reason that they claimed that traveling in this area was extremely dangerous. The city of Peć was the seat of the kaza and at the beginning of 1899 it was the center of gathering of Albanians, united around the goals directed against the Serbian population. In January of that year, numerous Albanians from various regions met and held a meeting, where they spoke about opposition to reforms and the expansion of tribal self-governance.Through influential beys, Porta emphasized the importance of unity and joint action against possible attacks from Serbia and Montenegro. The agreement between them caused concern among the Serbs and hinted at even greater insecurity. The position of the Serbian population was negatively affected by the Albanians agreements, but also by mutual conflicts. This is best illustrated by the event that took place in the village of Verići, in which ten out of twelve Serbian houses were set on fire. The injured asked for help from the vali, the mutasarrif, the consuls of Serbia and Russia as well. Because of those events, the Kosovo vali Hafis Pasha came to Peć in the summer of the same year, but he did not take vigorous measures to prevent further suffering of the Serbs. His stay was mainly limited to daily meetings with Zejnul bey Mahmutbegović and the key figure in this area, Mula Zeka, whose views influenced the vali’s decisions. During vali’s mission in Peć, there happened atrocities on a much wider scale, which had never happened before. It was a very turbulent period of time marked by numerous sufferings, murders, blackmail, fines and expulsions of the Serbian population from those areas. Albanians were always ready to cause new disturbances, disobedience and non-payment of taxes, which affected the weakening of the state. Among the most persistent were the Fetahović brothers, Colj Sokol, Jusuf, Mula Zeka, Adem Zajim, Ibrahim Mehmed Redžić and others. They contributed to the removal of the energetic officer Šemsi Pasha from Peć and the removal of Peć’s mutesarrif Suleiman Pasha, who was replaced by Alil Pasha, the former commissioner on the Serbian-Turkish border. Sultan Abdul Hamid and the Porta constantly favored the Albanians and instead of punishing the criminals, numerous decorations and ranks were awarded from Constantinople. The continuous support of the sultan and the Turkish authorities incited the Arbanas of Peć to new acts of violence. In just two years, 1900 and 1901, crimes of apocalyptic proportions took place against the Serbs in the Kosovo Vilayet, of which the most victims were in Peć kaza. The reason lies in the fact that, in addition to the Albanians terror, the victims were also exposed to daily attacks by the Roman Catholic Albanians, who were susceptible to Austrian propaganda. The Albanians leader Mula Zeka, was considered an Austrian mercenary and dominated the situation in the entire Peć kaza, where, according to the estimate of the consulate of the Kingdom of Serbia in Priština, there were no more than 1,500 Serbian families at the beginning of the 20th century. Exposed to terror, the Serbs of Peć kaza fled from their homesteads. Many of them fled to Serbia, and some moved to other places in the territory of the Kosovo Vilayet, where their fate was still uncertain. The emigration continued later and according to the assessment of the Serbs of Peć kaza from 1907, in the previous twenty years, 20,000 people emigrated to Serbia and Montenegro, instead of whom Mula Zeka settled 300 Arbanas families from Malesia.